Results of treatment with topical mitomycin C 0.02% following excision of primary pterygium. Issue 3 (March 1995) - Rachmiel, R; Leiba, H; Levartovsky, S
Abstract : AIMS--The effectiveness of instillation of mitomycin C eyedrops on the recurrence rate of pterygium was assessed in patients undergoing primary pterygium surgery. Any side effects were also noted. METHODS--Primary pterygia in 38 consecutive patients were surgically excised during July to December 1992. After surgery, mitomycin C 0.02% eyedrops twice daily for 5 days as well as dexamethasone 0.1% four times tapered for the next 6 weeks were instilled. Postoperative follow up ranged from 6 to 11 months. RESULTS--In one patient the pterygium recurred after 3 months (recurrence rate 2.6%). The side effects encountered were: avascularised sclera in 13 cases between 1-10 months postoperatively; ocular discomfort and lacrimation in five cases; superficial punctate keratitis during the first month in three cases; pyogenic granuloma in two cases. In one patient steroid induced increased intraocular pressure was found 4 weeks after surgery. The adverse side effects were all mild, self limiting, and easily treated. CONCLUSION--This study suggests that postoperative instillation of mitomycin C 0.02% eyedrops twice daily for 5 days following excision of primary pterygium is an effective and safe treatment to obviate pterygium recurrence.